Entrepreneurship Training for Kampung Pisang Nagari Koto Panjang Kecamatan IV Koto Communities: Pelatihan Kewirausahaan Bagi Masyarakat Kampung Pisang Nagari Koto Panjang Kecamatan IV Koto - Anne Putri; Kuliman; Aries Tanno; Adriani Adnani; Mairinal Avis; Ananda Yuliska Rahma; Ilham Wahyudi; Laravia Nendri (KPN Kopertis X, 2023)
Kampung Pisang is included in Nagari Koto Panjang, District IV Koto, according to its name, bananas are the main product of this village. Bananas with a distinctive taste are mostly sold to Bukittinggi in unprocessed raw form. The people in Nagari Koto Panjang are MSME actors engaged in selling bananas, but there is a lack of motivation for the people in Nagari Koto Panjang in developing their business. The implementation of PKM in Pisang Village aims to increase the creativity and innovation of MSME actors in Nagari Koto Panjang to create a wide variety of varied products and market their products to a wider network. It is hoped that in the future the people in Nagari Koto Panjang will be able to increase the variety of their products